Microsoft Team Foundation server 2015 cookbook : over 80 hands-on DevOps and ALM-focused recipes for scrum teams to enable the continuous delivery of high-quality software ... faster! /: over 80 hands-on DevOps and ALM-focused recipes for scrum teams to enable the continuous delivery of high-quality software ... faster!. (2016) - Arora, Tarun
No abstract available